Implementasi pendidikan karakter religius dan peduli lingkungan pada peserta didik di sekolah dasar - Susanti, Susanti; Chumdari, Chumdari; Suharno, Suharno (Didaktika Dwija Indria, 2022)
This research is entitled the implementation of religious character education and environmental care in sixth grade students of Integrated Elementary School Ma’arif Gunungpring Magelang for the 2022/2023 academic year. The aims of this study are to describe the forms and results, supporting and inhibiting factors, and solutions to overcome obstacles in the implementation of religious character education and environmental care in the sixth grade of Integrated Elementary School Ma'arif Gunungpring. This research uses a qualitative descriptive approach. Data collection techniques use observation, interviews, documentation, and questionnaires. The results of this study show that the value of religious character and environmental care was developed through routine activities, spontaneity, conditioning, exemplary, integration in Lesson Plan and learning, as well as through school culture. The conclusion of this research is the spiritual attitude and environmental care of sixth grade students in the category of already entrenched.